2018
DOI: 10.1007/s10396-018-0877-y
|View full text |Cite
|
Sign up to set email alerts
|

There is a significant relationship between morning blood pressure surge and increased abdominal aortic intima–media thickness in hypertensive patients

Abstract: Abdominal A-IMT increased at a significant rate in patients with HT. An independent association was found between MBPS and A-IMT, which can both be easily detected by ABPM and B-mode USG. The high MBPS level was considered to be a simple and inexpensive method for detecting subclinical target organ damage. A-IMT measurement should also be a part of abdominal USG, which is a routine examination in HT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…AA-IMT measurement can be used to detect the development of early atherosclerosis due to the initial onset of atherosclerosis in the distal abdominal aorta [3][4][5]. There are limited studies regarding the usage of AA-IMT in patients with coronary artery disease (CAD) risk factors [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AA-IMT measurement can be used to detect the development of early atherosclerosis due to the initial onset of atherosclerosis in the distal abdominal aorta [3][4][5]. There are limited studies regarding the usage of AA-IMT in patients with coronary artery disease (CAD) risk factors [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently published articles have reported that AA-IMT may be easily measured with high-resolution devices [8][9][10][11]. Another important and atherosclerotic process-related IMT measurement region is thoracic aortic IMT (TA-IMT).…”
Section: Introductionmentioning
confidence: 99%
“…When the presence of collagen in the vein wall is examined; there are thin collagen fibril bundles in the subendothelial intima layer, more in the tunica media layer among the smooth muscle cells and much in the adventitia layer 21 . The most frequent causes of death in patients with acromegaly is are CV events and CV mortality is doubled compared to the normal population [1][2][3][4] . Therefore, it is important to diagnose these patients with increasing IMT at the stage of subclinical or asymptomatic atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The most important problem about the AIMT assessment in research studies is that AIMT measurement cannot be done clearly and there are not enough devices that provide adequate tissue penetration 22,23 . However, this measurement can be done clearly after 6 hours of fasting and in non-obese patients 2 . Atherosclerosis begins with fatty streaks in childhood, which can be detected early by sensitive vascular imaging techniques 16,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The common carotid artery intima-media thickness (IMT) and abdominal aortic IMT were calculated as previously described. (28) Grey-scale B-mode US evaluation was first performed to assess kidney sizes, cortical thickness and parenchyma echogenicity. Kidney length was measured in the coronal plane from the upper pole to the lower pole of the kidney.…”
Section: Methodsmentioning
confidence: 99%